How debris‐flow composition affects bed erosion quantity and mechanisms: An experimental assessment. Issue 8 (20th April 2022) - Roelofs, Lonneke; Colucci, Pauline; de Haas, Tjalling
Abstract: Understanding erosion and entrainment of material by debris flows is essential for predicting and modelling debris‐flow volume growth and hazard potential. Recent advances in field, laboratory and modelling studies have distilled two driving forces behind debris‐flow erosion: impact and shear forces. How erosion and these forces depend on debris‐flow composition and interact remains unclear. Here, we experimentally investigate the effects of debris‐flow composition and volume on erosion processes in a small‐scale flume with a loosely packed bed. We quantify the effects of gravel, clay and solid fraction in the debris flow on bed erosion. Erosion increased linearly with gravel fraction and volume, and decreased with increasing solid fraction. Erosion was maximal around a volumetric clay fraction of 0.075 (fraction of the total solid volume). Under varying gravel fractions and flow volumes erosion was positively related to both impact and shear forces, while these forces themselves are also correlated. Results further show that internal dynamics driving the debris flows, quantified by Bagnold and Savage numbers, correlate with erosional processes and quantity. Impact forces became increasingly important for bed erosion with increasing grain size. The experiments with varying clay and solid fractions showed that the abundance and viscosity of the interstitial fluid affect debris‐flow dynamics, erosional mechanisms and erosion magnitude. High viscosity of the interstitial fluid inhibits the mobility of the debris flow, the movement of the individual grains and the transfer of momentum to the bed by impacts, and therefore inhibits erosion. High solid content possibly decreases the pore pressures in the debris flow and the transport capacity, inhibiting erosion, despite high shear stresses and impact forces. Our results show that bed erosion quantities and mechanisms may vary between debris flows with contrasting composition, and stress that entrainment models and volume‐growth predictions may be substantially improved by including compositional effects. Abstract : The erosion of unconsolidated sediment by debris flows is highly impacted by debris‐flow composition and volume. Internal dynamics and erosion mechanisms of the debris flow are dictated by shear and impact forces that are amplified or decreased by debris flow composition. In general, an increase in gravel content increases impact forces and erosion, and a small increase in clay content amplifies flow mobility and erosion, whereas a large increase in clay content decreases mobility and erosion, similar to a general increase in solid content.